A Regular City - Sharavina, Arina (project baikal, 2015)
The article describes the first plans of Chita, which served as the basis for the city development. It presents contribution to the city history made by the Decembrist Dmiry Zavalishin’s, who was the first author of the city development plan. Peculiarities of the quarter development of the realized city plan are also presented.
Keywords: Chita; Dmitry Zavalishin; topographic plan; city plan; Hyppodamus system; quarter; regular city